general analysis of the translation of Manuel Puig‘s Heartbreak Tango to German - Quintero, Andrés Felipe (Íkala, Revista de Lenguaje y Cultura, 2016)
The purpose of this paper is to compare the German translation of the novel Heartbreak Tango (1969) with its original in Spanish, in order to analyze the methods and procedures used by translator Adelheid Hanke-Schaefer. For purposes of extension, the passages of the novel under consideration were only those ones that were deemed to serve as an example and framework to detect, as far as possible, the challenges, doubts and other inconsistencies, often inevitable that may have emerged in the German version. In turn, this process is a pretext to ponder upon translation in general.